Investigating the Influence of Small-Scale Enterprises in the Industrial Advancement of Ogun State - Segun Kehinde (MultiTech Publisher, 2023)
This research investigation delves into the influential role of small-scale enterprises in propelling the industrial development of Ogun State, Nigeria. Small-scale enterprises (SSEs) are pivotal contributors to economic growth, innovation, and job creation. This study examines their impact on the industrial landscape, focusing on key dimensions such as local industrial growth, employment generation, and technology diffusion. The study also explores challenges encountered by SSEs and identifies potential strategies for harnessing their potential more effectively. The findings of this research hold practical implications for policymakers, entrepreneurs, and stakeholders keen on fortifying the industrial sector of Ogun State. Recognizing the dynamic influence of SSEs on industrial growth allows for informed decision-making and targeted policies to promote sustainable industrial development and economic prosperity within the state.